2021
DOI: 10.35445/alishlah.v13i3.971
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Using Kahoot! on Understanding the Concept of Mathematical Symbols in Higher Education

Abstract: This research was motivated by the condition of Mathematics Education students who were unfamiliar and unable to read and use these mathematical symbols correctly. This study aimed to examine the effect of Kahoot! game media on students’ understanding of concepts, especially on mathematical symbols. The population of this study was students of the Mathematics Education Study Program at Pahlawan Tuanku Tambusai University. At the same time, the research sample was 100 people obtained through random sampling, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…According to the present study's findings, researchers frequently described Kahoot! as an enjoyable, entertaining, and even amusing tool [3,9,30]. Furthermore, according to a study conducted by Pratama, et al [8] it was found that individuals who participated in Kahoot!…”
Section: Facilitatingmentioning
confidence: 99%
“…According to the present study's findings, researchers frequently described Kahoot! as an enjoyable, entertaining, and even amusing tool [3,9,30]. Furthermore, according to a study conducted by Pratama, et al [8] it was found that individuals who participated in Kahoot!…”
Section: Facilitatingmentioning
confidence: 99%
“…These teachers believe that video games should be used. Recent meta-analyses, on the other hand, previous study suggest that the use of games in mathematics JPI P-ISSN: 2303-288X E-ISSN : 2541-7207 instruction has only a small and only marginally significant positive influence on the learning of the students (Wahyuni et al, 2021). The game possibilities that have been discussed but not yet implemented have not been implemented.…”
Section: Introductionmentioning
confidence: 99%
“…The usage of games, which have been around for a very long time and have been the focus of research for a number of years, is a component of mathematical education (Campilla & Castañaga, 2021;Su et al, 2022;Wahyuni et al, 2021). One study found that the use of games in the classroom setting of mathematics is substantially higher than that of any other subject.…”
Section: Introductionmentioning
confidence: 99%
“…increases motivation in mathematics lessons (Setiawan & Soeharto, 2020). Wahyuni et al (2021) found that the application improved the conceptual understanding of pre-service mathematics teachers.…”
Section: Introductionmentioning
confidence: 99%